Scientometric and Patentometric Analysis to Determine the Knowledge Landscape in Innovation Technologies: The Therapeutic Ultrasound Equipments - Aguilar-Juárez, V.; Sánchez-Colín, M. A.; Zúñiga-Avilés, L. A. (Revista Mexicana de Ingenieria Biomedica, 2020)
This paper proposes an information model to determine the panorama of emerging technologies related to ultrasound equipment, which allows the identification of four main categories of research and development within the field, using a competitive methodology that incorporates the evaluation of scientific publications and a patent analysis; by using different databases by keywords clustering and years relevance. Google Scholar, Scopus, Springer, Sage Journals, ScienceDirect and Academic.edu databases were examined to consult articles and scientific publications; about 67,000 articles were found, of which only 119 met the exclusion criteria, the different parts of an ultrasound equipment, its different applications and new trends were analysed. The databases of Patentscope, Google Patents, and Invenes, as well as the bases of WIPO and USPTO were used for the recollection of patents; in which about 421 patents were found in relation to ultrasound equipment, the country in which the patent was registered and the way it is classified. Finally, only 16 patents meet the exclusion criteria. The results show USA as the country with the most diffusion rate in publishing articles and patents.